Weather-resistant and durable coating composition

The curing coating composition with amino-functional silicone resin and acrylico polymer addresses hydrolysis issues in isocyanate-based coatings, providing enhanced stability, UV protection, and corrosion resistance, while maintaining cost-effectiveness and substrate compatibility.

JP7621355B2Active Publication Date: 2025-01-24DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022529100
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-05
Filing Date
2020-11-12
Publication Date
2025-01-24
Estimated Expiration
2040-11-12

AI Technical Summary

Technical Problem

Existing coatings that require isocyanates for weather resistance and durability face issues with hydrolysis in the presence of water, leading to brittleness and instability, and alternative coatings lack a balance of UV protection, corrosion resistance, and drying time while being cost-effective.

Method used

A curing coating composition comprising an amino-functional silicone resin with specific molecular structures and an acrylico polymer, combining epoxy and functional groups to provide stability and performance characteristics without isocyanates, using Si-O-C bonds for improved durability and incorporating aryl groups for enhanced properties.

Benefits of technology

The composition achieves improved stability, UV protection, corrosion resistance, and drying time with minimal materials, offering high-quality, cost-effective coatings suitable for various substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621355000001
    Figure 0007621355000001
  • Figure 0007621355000002
    Figure 0007621355000002
  • Figure 0007621355000003
    Figure 0007621355000003
Patent Text Reader

Abstract

A curable coating composition is provided that includes a multifunctionalized acrylic copolymer and an amino-functional silicone resin curing agent. The acrylic copolymer of the curable coating composition has, in polymerized form, epoxy-functionalized groups and curing-compatible groups, and the amino-functional silicone resin is an aryloxy-containing amino-functional siloxane, which optionally derives from a sterically hindered alcohol-amine precursor moiety. The coating composition is useful in the field of superior weather resistance and durability coatings and as an alternative to isocyanate-containing polyurethane-based coatings. Coated articles made from the curable composition are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable coating composition having a multifunctionalized acrylic copolymer and an amino-functional silicone resin curing agent. More specifically, the acrylic copolymer has epoxy-functionalized groups and curing compatible groups in polymerized form, and the amino-functional silicone resin is an aryloxy-containing amino-functional siloxane, which is also optionally derived from a sterically hindered alcohol-amine precursor moiety. The coating composition is useful in the field of excellent weather resistance and durability coatings, and is useful as a replacement for isocyanate-containing polyurethane-based coatings.

[0002] Isocyanate-containing polyurethane-based coatings are used in applications where excellent weather resistance and durability are required. However, manufacturers and consumers are hoping to move to isocyanate-free coatings to limit exposure to such materials while still providing weather resistance in addition to chemical and corrosion resistance. Epoxy coatings are used to protect metals, but in applications where good color and gloss retention is required, the epoxy coating is further coated with a topcoat, most often a polyurethane. Other coatings derived from epoxy resins, such as polysiloxane-epoxy coatings, are dependent on humidity for curing and often become brittle as the coating continues to cure.

[0003] Some amino-functional polysiloxanes with amine functionality also incorporate aryl-containing groups, such as phenyl groups, to improve coating performance attributes and compatibility with coating components. Amine functional groups can be connected via Si-C and / or Si-O-C bonds, but connections via Si-O-C bonds typically present stability concerns in the presence of moisture, as the SiOC bond is susceptible to hydrolysis, regenerating the original amine alcohol and silanol. Hydrolysis affects both the appearance of the protective coating, since the alcohol amines are typically incompatible with the host siloxane resin and organic epoxy hardener, and the performance of the protective coating, since the level of chemical crosslinking is greatly limited when the SiOC bond is broken. Aryl-containing groups, such as phenyl groups, typically connect to the polysiloxane via costly Si-C bonds.

[0004] US2005 / 0148752 A1 discloses amino-functional polysiloxanes having Si-O-C bonds between the polymer backbone and the functional groups, including epoxy polysiloxane compositions. US2005 / 0148752 A1 fails to identify coatings containing acrylic copolymers. Furthermore, US2005 / 0148752 A1 fails to distinguish the advantages associated with the use of siloxanes derived from sterically hindered alcohol-amine precursor moieties from non-sterically hindered moieties.

[0005] US Patent No. 8,012,543 discloses the use of polyorganosiloxanes modified with aminoalcohols to reduce corrosion of rebar in concrete structures, where the polyorganosiloxanes may contain alkyl or aryl radicals, including phenyloxy radicals. US Patent No. 8,012,543 fails to identify coatings that contain acrylic copolymers.

[0006] US 2017 / 0174938 A1 discloses the use of a coating layer composition containing a silsesquioxane complex polymer to prevent substrate warpage, some embodiments of which contain SiOC amine and SiOC aryl groups. US 2017 / 0174938 A1 fails to identify coatings that include acrylic copolymers.

[0007] U.S. Pat. No. 8,193,293 discloses a low temperature ambient curable coating composition comprising an amino-functional polysiloxane, a polysiloxane resin which is the reaction product of a polysiloxane containing silicon hydride and a hydroxyl-functional material having two or more unsaturated bonds capable of undergoing hydrosilylation reactions, and a polyepoxide.

[0008] U.S. Patent No. 8,871,888 discloses a high solids, one-component, storage stable coating composition comprising an epoxy resin containing two or more 1,2-epoxy groups per molecule, a hydrocarbon compound having a softening point of 50°C to 140°C, an alkoxy-functional and / or silanol-functional silicone, and a ketimine hardener comprising the reaction product of a reactant comprising a polyalkyldiamine component and a ketone component.

[0009] WO 01 / 51575 A1 discloses an ambient temperature curing coating composition comprising a polysiloxane having alkyl, aryl, alkoxy, reactive glycidoxy, and OSi(OR)3 groups, a glycidyl-functional acrylic polymer, and a curing agent. The polysiloxane does not contain amine functionality.

[0010] Japanese Patent Publication No. 2002-167546 A discloses a corrosion-resistant coating material composition for single-coat finishing, comprising (A) an acrylic resin, (B) an epoxy resin having at least two epoxy groups, (C) an organosilane compound, and (D) an aminosilane-containing amine hardener, in which the blending ratios of the acrylic resin (A), the epoxy resin (B), and the organosilane compound (C) are 5-65% by weight for component (A), 30-90% by weight for component (B), and 5-65% by weight for component (C), based on the total solid content of each of these resins.

[0011] What is needed is a cost-effective coating composition that exhibits good stability in the presence of moisture and provides a good balance of properties including UV protection, corrosion resistance, good dry time, and chemical resistance, all using a minimum of materials.

[0012] The present invention provides a curable coating composition comprising: (1) In polymerized form (i)(RSiO 1 / 2 ) a , (ii) (R2Si(OR') x O (2-x) / 2 ) b , (iii) (RSi(OR') y ,O (3-y) / 2 ) c , and (iv) (Si(OR') z O (4-z) / 2 ) d , wherein each R′ is independently hydrogen, an alkyl group, a functionalized alkyl group, an aryl group, or a functionalized aryl group, with the proviso that at least 10 mole percent of all R′ groups are aryl groups or functionalized aryl groups, wherein each R is independently hydrogen, an alkyl group, or a functionalized alkyl group, and wherein at least 10 mole percent of the combination of the R and R′ groups are of the formula: -R a -NHR bwhere R a is an alkyl or aryl-containing group derived from an amino alcohol, R b is hydrogen or an alkyl group, where a+b+c+d=1.00 (100 mole percent), x is either 0 or 1, y is either 0, 1, or 2, and z is either 0, 1, 2, or 3; and the -NH- equivalent weight of the amino-functional silicone resin is 50 to 750; and (2) an acrylic copolymer having, in polymerized form, epoxy functionalized groups and curable compatible groups, wherein the coating composition has an amine NH functionality in the range of 0.5 to 1.3. of Epoxy Functional Group for The present invention further provides a coating article comprising one or more layers of the cured coating composition.

[0013] The term "mole percent" can also be expressed as "mole fraction", with 1 mole percent equal to a mole fraction of 0.01. The terms "mole percent" and "mole fraction" are based on the Si content in a material totaling 100 mol% (i.e., 1.00 mole fraction). For each range provided herein, the lower limit of the range and the upper limit of the range can be separated and combined in any manner with other lower or upper limits, including combinations of lower and upper limits of ranges of additional components specified herein. All individual values ​​and subranges are included herein and disclosed herein.

[0014] Amino-functional silicone resin The amino-functional silicone resins of the present invention can be described as siloxane structures having siloxane linkages (-Si-O-Si-) with aryl functional groups connected to Si units on the siloxane structure via Si-O-C bonds and amine functional groups connected to either Si units on the siloxane structure via Si-O-C bonds or Si-C bonds to Si units on the siloxane structure, or some combination of the two, which in polymerized form are (i)(RSiO 1 / 2 )a , (ii) (R2Si(OR') x O (2-x) / 2 ) b , (iii) (RSi(OR') y ,O (3-y) / 2 ) c , and (iv) (Si(OR') z O (4-z) / 2 ) d wherein each R' is independently hydrogen, an alkyl group, a functionalized alkyl group, an aryl group, or a functionalized aryl group, provided that at least 10 mole percent of all R' groups are aryl groups or functionalized aryl groups; wherein each R is independently hydrogen, an alkyl group, or a functionalized alkyl group; wherein at least 10 mole percent of the combined R and R′ groups are of the formula: -R a -NHR b where R a is an alkyl or aryl-containing group derived from an amino alcohol, R b is hydrogen or an alkyl group, where a+b+c+d=1.00 (100 mole percent), x is either 0 or 1, y is either 0, 1, or 2, and z is either 0, 1, 2, or 3; The --NH-- equivalent weight of the amino-functional silicone resin is 50-1000, preferably 50-750, more preferably 80-900, even more preferably 100-800, and most preferably 100-700.

[0015] The R and / or R′ groups are of the formula: a -NHR b It can be an amine-containing group of the formula: -R a -NHR bThe amount of all R and R' groups that are amine-containing groups can be as low as 10 or 20 mole percent and independently as high as 90, 50 or 30 mole percent, with preferred ranges of 10 to 42 mole percent and 20 to 30 mole percent, provided that the -NH- equivalent weight of the amino-functional silicone resin is within the ranges specified. a is the formula HO-R a -NHR b wherein R a is an alkyl group or an aryl-containing group. a is derived from an amino alcohol selected from the group of: (a) amino alcohols that are sterically hindered around the COH moiety, (b) amino alcohols that are secondary or tertiary alcohols, or (c) mixtures thereof.

[0016] The amount of all R' groups that are aryl or functionalized aryl groups can be as low as 10 or 20 mole percent and, independently, as high as 100, 50 or 30 mole percent, with preferred ranges being 10 to 60 mole percent and 20 to 50 mole percent.

[0017] In the description of silicone resin, RSiO 1 / 2 is also called M and RSiO 2 / 2 is also called D and RSiO 3 / 2 is also called T, and SiO 4 / 2 is also referred to as Q. When a superscript is used next to the M, D, T, or Q symbol, it refers to the type of R group that is present. For example, D Ph means that one of the two R groups is a phenyl group. Any R group(s) without a superscript would be understood by one of ordinary skill in the art to be a methyl group, unless the specific description of the polymer dictates otherwise. The -NH- equivalent weight of an amino-functional silicone resin is determined by the mass of a known amount of solution or neat sample of the amino-functional silicone resin. 13The C-NMR spectrum is obtained and the peaks associated with the amino-functional Si units of the amino-functional silicone resin are quantified against peaks associated with a known amount of an internal standard (typically 1,4-dioxane), adjusting for any solvent content present in the sample as determined by gas chromatography. The amino-functional silicone resin may be in the form of a neat liquid, a solution, or a meltable solid. Each subscript a, b, c, or d is an average value across the distribution of units that make up the material and is used to determine the NMR spectrum data (typically, 29 Si-NMR and 13 C-NMR, or 29 Si-NMR and 1 It can be determined for any given material by using calculations based on 1 H-NMR.

[0018] The amino-functional silicone resin of the present invention can be made by reacting (1) a silicone resin having hydroxyl or alkoxy functionality with (2) an amino alcohol and an aryl alcohol. The silicone resin having hydroxyl or alkoxy functionality can be derived from polysiloxane, alkoxysilane, or chlorosilane. The hydroxyl or alkoxy functionality of the silicone resin (1) composition is sometimes referred to as the "OZ" content and is expressed in mole percent. Non-limiting examples of suitable silicone resins include DOWSIL™ 2403, DOWSIL™ 3074, and DOWSIL™ 3037 available from The Dow Chemical Company, Shin-Etsu Silicone KR-213 and KR-510 available from Shin-Etsu Chemical Co., Ltd., and SILRES® IC232 and SILRES® SY231 available from Wacker Chemie AG.

[0019] The amino alcohols, as described above, have the formula HO-R a -NHR bNon-limiting examples of suitable amino alcohols include 2-amino-1-ethanol, 1-amino-2-propanol, 1-amino-2-methylpropan-2-ol, 2-amino-1-propanol, 3-amino-1-propanol, 2-amino-1-butanol, 3-amino-1-butanol, neopentanolamine (3-amino-2,2-dimethyl-1-propanol), 2-amino-1-methyl-1-propanol, 2-amino-2-methyl-1-propanol, 2-amino-2-ethylpropane-1,3-diol, 2-amino -2-Methylpropane-1,3-diol, 5-amino-1-pentanol, 1,2-dimethylethanolamine, 3-alloxy-2-hydroxy-propylamine, 1-amino-2-methyl-pentanol, N-methylethanolamine, N-hydroxyethylpropanediamine, N-cyclohexylethanolamine, p-(beta-hydroxyethyl)-aniline, N-(beta-hydroxypropyl)-N'-(beta-aminoethyl)piperazine, 2-hydroxy-3-(m-ethylphenoxy)propyl Amines, 2-hydroxy-2-phenylethylamine, tris(hydroxymethyl)aminomethane, 2-aminobenzyl alcohol, 3-aminobenzyl alcohol, 3-amino-o-cresol, 4-amino-o-cresol, 5-amino-o-cresol, 2-amino-p-cresol, 4-amino-m-cresol, 6-amino-m-cresol, 1-amino-1-cyclopentanemethanol, 2-(2-aminoethoxy)ethanol, 2-(2-aminoethylamino)ethanol, 6-amino-1-hexanol, 3-(1 -hydroxyethyl)aniline, 2-amino-1-phenylethanol, 1-aminomethyl-1-cyclohexanol, 8-amino-2-naphthol, 2-amino-phenethyl alcohol, 4-aminophenethyl alcohol, 3-(alpha-hydroxyethyl)aniline, Mannich bases, products of the reaction of aminoalcohols with cis-2-pentenenitrile followed by a hydrogenation step, aminophenols such as p-aminophenol, tyrosine, tyramine, etc., epoxyamine adducts, and mixtures thereof.Preferred amino alcohols include, but are not limited to, 1-amino-2-propanol and 1-amino-2-methylpropan-2-ol.

[0020] NMR: The composition of various aryloxy-containing amino-functional silicone resin compositions is determined using NMR. Nuclear magnetic resonance (NMR) analysis is performed using a Mercury 400 MHz superconducting spectroscopy instrument. The instrument uses a silicon-free probe.

[0021] Aryloxy Content - The aryloxy content is calculated from 13C NMR data using deuterated chloroform as an internal standard. The weight of resin and chloroform added to the NMR sample is used to determine the weight percent aryloxy. This information is 29 Used in conjunction with the composition obtained from Si NMR, the molar amount of aryloxy is calculated.

[0022] Molecular Weight - Resins analyzed for molecular weight (Mn and Mw) are performed using gel permeation chromatography. Samples are prepared in THF at 0.5% concentration, capped with acetic anhydride, filtered, and analyzed against polystyrene standards using RI detection. The columns are two 300mm 5 micron Mixed C with a 50mm guard column. The flow rate is 1ml / min.

[0023] The alkyl groups are exemplified by, but not limited to, methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, dodecyl, hexadecyl, and octadecyl, and the alkyl groups are typically methyl. The aryl groups are exemplified by, but not limited to, phenyl, naphthyl, benzyl, tolyl, xylyl, xenyl, methylphenyl, 2-phenylethyl, 2-phenyl-2-methylethyl, chlorophenyl, bromophenyl, and fluorophenyl, and the aryl groups are typically phenyl.

[0024] Silicone resins having hydroxy, alkoxy or aryloxy functional groups are synthesized according to polymerization methods known in the art. Non-limiting exemplary polymerization methods are disclosed in U.S. Patent Publication No. 2005 / 0148752 A1.

[0025] Description of polyfunctional acrylic copolymers By multifunctionalized acrylic copolymer is meant a copolymer containing a majority of copolymerized (meth)acrylic esters, including acrylate linkages, epoxy functionalized groups, and polymerized forms via cure compatibility groups, which retain functionality on the backbone of the acrylic copolymer. Preferably, the multifunctionalized acrylic copolymer is a polar material, due in part to the presence of cure compatibility groups, which is believed, without being bound by any theory, to aid in compatibility with polar aryl-containing, amino-functional silicone resins. This compatibility is best seen by the reduced haze of the cured coating composition. As used herein, the use of the term "(meth)" followed by another term, such as acrylate, refers to both acrylates and methacrylates. For example, the term "(meth)acrylate" refers to either acrylates or methacrylates. Similarly, the term "(meth)acrylic acid" refers to methacrylic acid or acrylic acid. Acrylic copolymers may be prepared by free radical polymerization in a solvent such as xylene by charging the monomers, initiator, optionally a chain transfer agent, and solvent into a vessel and reacting at about 60°-175° C. for about 1-6 hours to form the polymer. Typical solvents that may be used to prepare the acrylic copolymers are the following: toluene, ethyl acetate, butyl acetate, acetone, methyl isobutyl ketone, methyl ethyl ketone, ethyl alcohol, mineral spirits, ethylene glycol monoethyl ether acetate, and other aliphatic, cycloaliphatic, and aromatic hydrocarbons, esters, ethers, ketones, and alcohols, which are conveniently used. Alternatively, the acrylic copolymers may be prepared via free radical emulsion or suspension addition polymerization, or by dispersing a preformed polymer in an aqueous medium under shear. Preferably, the acrylic copolymers of the present invention are solvent-based.

[0026] Suitable monomers for preparing acrylic copolymers include (meth)acrylates, such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and combinations thereof. Additional monomers can be used to prepare acrylic copolymers, including carboxylic acid monomers such as (meth)acrylic acid and itaconic acid, and their salts, sulfonic acid monomers such as sodium styrenesulfonate and sulfonic acid acrylamido-methyl-propane, and their salts, as well as phosphoric acid monomers such as phosphoethyl methacrylate and its salts. Monomers such as styrene, acrylonitrile, acetoacetoxyethyl methacrylate (AAEM), and alkoxysilane-functional (meth)acrylates, as well as monomers that can provide co-curable functional groups, such as glycidyl (meth)acrylate and hydroxyalkyl (meth)acrylate, can also be used in preparing acrylic copolymers. In certain embodiments, it may be advantageous to incorporate small amounts of copolymerized multiethylenically unsaturated monomer groups into the acrylic copolymer, including allyl (meth)acrylate, diallyl phthalate, 1,4-butylene glycol di(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and divinylbenzene. It may also be advantageous to incorporate such monomer groups non-uniformly into the polymer to form multiphase polymer particles and create core-shell, hemispherical, or occluded morphologies. Chain transfer agents may be used to prepare these acrylic copolymers, examples of which include dodecyl mercaptan, 2-mercaptoethanol, mercaptotrialkoxysilane, butyl mercaptopropionate, methyl mercaptopropionate, and mercaptopropionic acid. Initiators may be used to prepare these acrylic copolymers, examples of which include peroxy and azo compounds.

[0027] The epoxy functionalized group of the acrylic copolymer includes a glycidyl group, such as glycidyl methacrylate (GMA) or glycidyl acrylate, with GMA being preferred. The curing compatible group of the acrylic copolymer includes, in polymerized form, a monomer group that contains one or more of an alcohol (OH) functional group, a phenol group, a silicone group, a tertiary amine, such as in the monomer 3-(trimethoxysilyl)propyl methacrylate (MATS), or an acid group that is either pendant to the main chain (as in the case of the acrylic monomer) or connected as an end group, for example, in this case an OH-functional chain transfer agent is used in the polymerization. Preferably, the curing compatible group is hydroxyethyl (meth)acrylate (HEMA or HEA). Preferably, the acrylic copolymer is synthesized from monomers including GMA, HEMA, methyl methacrylate (MMA), and 2-ethylhexyl acrylate (EHA).

[0028] The acrylic copolymer contains 30-80% by weight of glycidyl (meth)acrylate monomer units, preferably 40-60% by weight of glycidyl (meth)acrylate monomer, most preferably more than 30% by weight at the bottom of the range, based on the weight of the total monomer units added to produce the copolymer. The acrylic copolymer contains up to 20% by weight of cure compatible group monomer units, preferably up to 10% by weight of cure compatible group monomer units, preferably up to 8% by weight of cure compatible group monomer units, preferably more than 2% by weight of cure compatible group monomer units, with a preferred range of 5-10% by weight. The upper limit of cure compatible group is determined primarily by the viscosity of the copolymer when HEMA is combined with GMA functionality. In theory, it would be possible to have a higher content of cure compatible group when using other monomers, such as a combination of HEA and glycidyl acrylate. The acrylic copolymer contains an epoxy equivalent weight (EEW), as determined according to ASTM D1652, in the range of 200 to 600 g / mol epoxy, preferably greater than 250 g / mol epoxy, more preferably greater than 275 g / mol epoxy at a lower limit, preferably less than 500 g / mol epoxy, more preferably less than 450 g / mol epoxy at an upper limit, with the preferred range being 300 to 400 g / mol epoxy.

[0029] The acrylic copolymers have a calculated glass transition temperature ("Tg") of eighty degrees Celsius (80°C) or less, preferably 30°C or less, and most preferably 15°C or less, with a preferred range of -40°C to 10°C. The Tg is arrived at by selection of monomers and amounts of monomers to achieve the desired polymer Tg, as is well known in the art. The Tg of a polymer is measured using dynamic scanning calorimetry.

[0030] The acrylic copolymer solutions are viscous liquids having viscosities ranging from 500 centipoise (cP) to 8,000 cP at about 70% solids at room temperature (25° C.). The acrylic copolymers of the present invention have a number average molecular weight of 500 to 10,000 g / mol, preferably 1,000 to 5,000 g / mol or more, or more preferably 4,000 g / mol or less, as measured by gel permeation chromatography using polystyrene standards.

[0031] Coating Composition Description The coating composition of the present invention comprises an acrylic copolymer and an amino-functional silicone resin. of Epoxy Functional Group for The molar ratio ranges from 0.5 to 1.3, preferably 0.8 to 1. Preferably, an excess of amine groups is best avoided as it can lead to amine blush which adversely affects exterior durability. Amine blush is a loss of gloss on exposure to water. The coating composition typically undergoes ambient cure, although accelerated cure is possible.

[0032] The coating compositions of the present invention may contain additional components including, but not limited to, accelerators / plasticizers such as benzyl alcohol, salicylic acid, and tris-2,4,6-dimethylaminomethylphenol; fillers such as finely divided minerals including silica, alumina, zirconia, talc, sulfates, TiO2, carbon black, graphite, silicates, and the like; other hardeners, other epoxy resins, reinforcing agents, rheology modifiers, solvents, accelerators, surfactants, ultraviolet (UV) stabilizers, antioxidants, wetting agents, solvents, defoamers, toughening agents, and colorants including pigments, dyes, and tints.

[0033] The curable coating compositions of the present invention can be unpigmented transparent clearcoats or pigmented systems for primer, basecoat, and topcoat applications. The pigments can be any typical organic or inorganic pigment. Several different pigments may be required to achieve the desired color for a particular application. Examples of suitable pigments include, but are not limited to, titanium dioxide, opaque polymers, barytes, clay, calcium carbonate, red iron oxide, CI Pigment Yellow 42, CI Pigment Blue 15, 15:1, 15:2, 15:3, 15:4 (copper phthalocyanine), CI Pigment Red 49:1, CI Pigment Red 57:1, and carbon black.

[0034] The resulting coating composition can be applied to a substrate using techniques known in the art, such as spraying, brushing, drawing down, and roll coating. The nominal dry film thickness (DFT) of the coating is 1 mil or more, preferably 2 mils or more, preferably 2.5 mils or more, and more preferably 3 mils or more. A mil is equal to 1 / 1000 of an inch. Examples of substrates that can be coated include, but are not limited to, plastic, wood, metal (such as aluminum, steel, or galvanized sheet), tin-plated steel, concrete, glass, composites, urethane elastomers, primed (painted) substrates, and the like. The coating can be cured at room temperature or at elevated temperatures in a forced air oven or using other types of heat sources.

[0035] The following examples illustrate the invention.

[0036] Examples and Experimental Methods: Acrylic Copolymer Xylene was added to a 500 mL 4-neck round bottom flask equipped with a stirring shaft, condensation apparatus, thermocouple port, and addition port. The temperature of the xylene was raised to reflux (140 °C) using a heating mantle. A monomer blend consisting of glycidyl methacrylate (GMA), methyl methacrylate (MMA), 2-ethylhexyl acrylate (EHA), and 2-hydroxyethyl methacrylate (HEMA) was weighed and mixed in a 500 mL glass jar, then divided equally into 50 mL plastic feed syringes with Luer-Lok connections. The initiator, tert-butyl peroxyacetate (TBPA, 50% in mineral spirits), was added to a single 50 mL plastic syringe and connected to the feed tubing via a Luer-Lok connection with a long feed needle attachment. A dual syringe pump was used to add the monomer mixture at a constant feed rate, and a single feed syringe pump was used to feed the initiator. The feed was started when the solvent was refluxing. The feed rate time and temperature depend on the half-life of the solvent and initiator. When the feed was depleted, the lines were flushed with a small amount of solvent. The run was continued for an additional hour to reduce the residual monomer and initiator to acceptable levels. Table 1 shows the acrylic copolymers made. [Table 1]

[0037] Characterization of acrylic copolymers GPC 2 mg / mL of sample was dissolved in tetrahydrofuran (THF) and the solution was filtered through a 0.2 μm PTFE syringe filter before injection. Molecular weight measurements were performed using GPC measured on an Agilent 1100 series equipped with a MIXED-D column (300X7.5mm) at a flow rate of 1.0 mL / min at 35 °C. An Agilent refractive index detector is used with Agilent's GPC / SEC software. Calibration was performed using 17 narrow PS standards from Polymer labs and fitted with a third order polynomial curve over the range of 3,742 kg / mol to 0.580 kg / mol.

[0038] E.E.W. EEW is measured according to ASTM D1652. The epoxy resin is dissolved in methylene chloride and titrated with standardized 0.1N perchloric acid (HClO4) in glacial acetic acid in the presence of excess tetraethylammonium bromide (TEAB) in acetic acid. Measurements were performed using a Metrohm 905 titrator and associated Tiamo titration software configured for EEW determination.

[0039] Percent Solids Label the bottom of a small aluminum pan, place the pan on a balance, and record its weight to the nearest 0.0001 gram. Using a pipette, evenly distribute approximately 0.5g-1.5g of sample into the pan. Record that weight as the initial (pan + sample). Before placing the sample in the oven, place it in a baking dish, clip it in place with a binder clip, and use a pipette to cover the resin with approximately 2 grams of toluene, then carefully place in a preheated Class A oven. After 2 hours, remove the baking dish and sample from the oven. Set the balance to zero, place the sample (and pan) on the balance, record the final weight, and calculate the solids content by the following formula: Solids %=(Final weight - Pot weight) / (Initial weight - Pot weight)*100

[0040] Glass transition temperature T g was measured with Differential Scanning Calorimetry DSC Q2000 V24.10 according to ASTM D7426 with a sample size of approximately 5-10 mg. The temperature profile was performed as follows: 10°C 5 min isotherm, 10°C / min ramp to -50°C, 5 min isotherm, 10°C / min ramp to 150°C, 5 min isotherm, Tg was analyzed using TA software.

[0041] viscosity Viscosity measurements were made using a Brookfield DV-III Ultra Viscometer with a Small Sample Adapter (SSA). The rheologically correct cylindrical geometry of the Small Sample Adapter provides very accurate viscosity measurements and shear rate determinations. For these samples, 9 mL of material was deposited into the cylinder, using spindle #31 or #34, and varying the speed to achieve approximately 25 Newton meters (N*m) of torque. Measurements were reported in centipoise (cP).

[0042] Amino-functional silicone resin Amino-functional silicone resins S1-S6 are shown in Table 2. Resins S1-S4 incorporate aryl groups by SiOC grafting, resin S5 incorporates aryl groups by SiC grafting, and resin S6 does not incorporate aryl groups. Resins S1, S3, and S4 incorporate amine functionality through SiC bonds, while resins S2, S5, and S6 incorporate amine functionality through SiOC bonds. Procedures for making resins S1-S6 are provided after Table 2. [Table 2]

[0043] S1:D 0.14 T NH2 0.22 T Me 0.64 (OBz) 0.21 , amine equivalent 261g / eq NH, 37mol% OMe, 20mol% OEt Reagents: Methyltrimethoxysilane (MTM)-Mw=136.22 Dimethyldimethoxysilane - Mw=120.22 Aminopropyltriethoxysilane - Mw=221.37 Benzyl alcohol - Mw = 108.14 g / mol, bp = 205°C

[0044] procedure: A 250 mL 2-neck round bottom flask was charged with the following: -MTM (80.96g, 0.594mols, 1.783mols OMe) -Dimethyldimethoxysilane (21.88g, 0.182mols, 0.364mols OMe) - 3-aminopropyltriethoxysilane, available from The Dow Chemical Company as Dowsil™ Z-6011 (48.78 g, 0.220 mols, 0.660 mols OEt) -Benzyl alcohol (22.25g, 0.206mols)

[0045] The flask was equipped with a magnetic stir bar and a Dean Stark apparatus attached to a water-cooled condenser. The mixture was compatible at room temperature. Starting at room temperature, deionized water (16.73 g, 0.929 mols) was added slowly. After exotherming to 46° C., it was heated with an aluminum block at a pot temperature of 65° C. for 1 hour. The temperature was then increased to distill off the alcohol to a pot temperature of 150° C. Amount of volatiles removed: 73.65 g. Heating was continued at 150° C. for 5 hours. 1.65 g of volatiles were removed within the first hour. None were collected after this time. The product was stripped on a rotovapor at an oil bath temperature of 120° C. and approximately 1.5-2 mm Hg. The product was a clear, colorless, viscous liquid at room temperature. Isolated yield: 100.5 g. 13 Amine equivalent weight calculated from C NMR spectrum: 261 g / mol NH. NMR analysis of the product: D 0.136 T PrNH2 0.219 T Me 0.645 , OZ content: 79.1 mol% (OMe=36.6 mol%; OEt=19.7 mol%; OBz=21.2 mol%; OH=1.6 mol%).

[0046] S2:T Me 0.99 (OBz) 0.2 (OCH(CH3)CH2NH2) 0.18, amine equivalent 297g / eq NH, 32.5mol% OZ) Reagents: Methyl-T resin (described below): 0.01 T Me 0.99 FW=83.52g / mol Si;OZ=71.77mol%(OMe=70.30mol%, OH=1.47mol%) 1-Amino-2-propanol - Mw=75.11, bp=160℃ Benzyl alcohol - Mw = 108.14 g / mol, bp = 205°C ●Xylene-ACS grade

[0047] procedure: ●The following was charged into a 250mL two-neck round-bottom flask: -Methyl-T Resin (84.89g, 1.016mols Si, 0.729mols OZ) -1-Amino-2-propanol (16.52g, 0.220mols) -Benzyl alcohol (22.21g, 0.205mols) -Xylene (36.67g)

[0048] The flask was equipped with a magnetic stir bar and a Dean Stark apparatus attached to a water-cooled condenser. The amount of xylene added results in a theoretical yield of 75% by weight in xylene. The reaction mixture was initially cloudy at room temperature, but cleared within 5 minutes at room temperature. -Theoretical amount of methanol that can be produced when reacting 100% BzOH with the amine: 13.62g. Heated with an aluminum block at a pot temperature of 135°C. The onset time was measured from when volatiles first began to collect in the Dean Stark apparatus, which corresponds to a pot temperature of 127°C. The reaction was heated to 135°C and then held at this temperature. Total time: 12 hours. Volatiles removed: 30 minutes - 3.81g, 1 hour - 6.28g, 2 hours - 8.39g, 3 hours - 10.06g, 4 hours - 10.55g, 5 hours - 10.77g. No volatiles were collected after 5 hours. Analysis of the 12 hour sample by 13C NMR showed that approximately 89% of the 1-amino-2-propanol had reacted with the silicone. Approximately 93% of the benzyl alcohol had also reacted with the silicone.

[0049] Preparation of methyl-T resin: T with a target of 75 mol% OMe Me 1 Resin Reagents: Methyltrimethoxysilane - Mw=136.22 Deionized water Trifluoromethanesulfonic acid, available from 3M as Fluorad™ FC-24 - Mw=150.08 g / mol, density=1.696 g / ml Calcium carbonate powder, particle size ≦50um, Mw=100.09g / mol

[0050] procedure: A 1 L 4-neck round bottom flask was charged with methyltrimethoxysilane (650.0 g, 4.772 mols Si, 14.315 mols OMe). FC24 (0.33 g, 192 uL) was added, which corresponds to 500 ppm. Starting at room temperature, deionized water (96.71 g, 5.368 mols) was added slowly. Exotherm to 64° C. Theoretical amount of methanol that can be produced: 344.0 g (assuming 100% hydrolysis and condensation). Heated at 65° C. for 2 hours. Distilled off 320.88 g of methanol to a pot temperature of 75° C. Calcium carbonate (1.32 g) was added to neutralize the FC24. This corresponds to 4 times the amount of FC24 added (by weight). Mixed for 2 hours while cooling to room temperature. Stripped the resin on a rotary evaporator. Oil bath temperature = 50°C, approximately 50-60 mmHg. Pressure filtration through a 142 mm diameter Magna, Nylon, Supported, Plain, 0.45 Micron filter at room temperature. Isolated yield: 394.0 g. The product was a clear, low viscosity liquid at room temperature. Molecular weight: Mn = 1,837; Mw = 2,838 (relative to polystyrene standards in THF). 29Si NMR analysis of the product: D Me2 0.010 T Me 0.990 , OZ = 71.77 mol% (70.30 mol% OMe, 1.47 mol% OH), FW = 83.52 g / mol Si. Methoxy content was calculated from 13C NMR using CDCl3 as internal standard.

[0051] S3: Amine siloxane resin with aryl groups attached via the SiOC using secondary alcohols and amine functional groups attached via SiC bonds Reagents: Methyltrimethoxysilane (MTM)-Mw=136.22 Dimethyldimethoxysilane - Mw=120.22 Aminopropyltriethoxysilane - Mw=221.37 DL-sec-phenethyl alcohol (sPhEtOH) - Mw = 122.17 g / mol, bp = 203-205°C

[0052] procedure: A 250 mL 2-neck round bottom flask was charged with the following: -MTM (77.25g, 0.567mols, 1.701mols OMe) -Dimethyldimethoxysilane (20.88g, 0.174mols, 0.347mols OMe) -Z-6011 (48.76g, 0.220mols, 0.660mols OEt) -sec-Phenethyl alcohol (25.10g, 0.205mols)

[0053] The flask was equipped with a magnetic stir bar and a Dean Stark apparatus attached to a water-cooled condenser. The mixture was compatible at room temperature. Starting at room temperature, deionized water (16.17 g, 0.898 mols) was added slowly. Allowed to exotherm to 43°C. Heated with an aluminum block at a pot temperature of 65°C for 1 hour. The temperature was increased to distill off the alcohol to a pot temperature of 150°C. Amount of volatiles removed: 67.98 g. Heating was continued at 150°C for 10 hours. Volatiles removed: 1 hour - 2.22 g, 2 hours - 3.57 g, 3 hours - 4.02 g, 4 hours - 4.22 g, 5 hours - 4.42 g. No volatiles were collected after the 5 hour period. The product was stripped on a rotary evaporator at an oil bath temperature of 120°C and approximately 1.5-2 mmHg.

[0054] Result: The product was a clear, slightly yellowish viscous liquid at room temperature. Isolated yield: 98.4 g. 13 Amine equivalent weight calculated from C NMR spectrum: 258 g / mol NH. NMR analysis of the product: D 0.135 T PrNH2 0.227 T Me 0.638OZ content: 78.5 mol% (OMe = 32.1 mol%; OEt = 23.9 mol%; sec-PhEtO = 20.1 mol%; OH = 2.4 mol%); 8.52 wt% OMe; 9.18 wt% OEt; 20.8 wt% sec-PhEtO; 13.3 wt% phenyl (from sec-PhEtO). OR values ​​calculated from 13C NMR data using CDCl3 as internal standard. T PrNH2 and T Me The Si mole fraction for was derived from 13C NMR data.

[0055] S4: Amine siloxane resin with aryl groups attached via the SiOC using a tertiary alcohol and amine functional groups attached via the SiC bond. Reagents: Methyltrimethoxysilane (MTM) - Mw = 136.22 g / mol Aminopropyltrimethoxysilane - Mw=179.29 2-Methyl-1-phenyl-2-propanol - Mw=150.22, bp=215℃ ●Xylene-ACS grade ●KOH (45% in water)-Mw=56.1g / mol HCl solution - 8.0N HCl in water was diluted with methanol to obtain a solution containing 0.000742mols HCl / gram.

[0056] procedure: A 250 mL 2-neck round bottom flask was charged with the following: -MTM (97.01g, 0.712mols, 2.136mols OMe) - Aminopropyltrimethoxysilane (39.40g, 0.22mols, 0.659mols OMe) -2-Methyl-1-phenyl-2-propanol (39.85g, 0.265mols)

[0057] The flask was equipped with a magnetic stir bar and a Dean Stark apparatus attached to a water-cooled condenser. Added 1.8x MePhPrOH. Starting at room temperature, slowly added deionized water (17.14g, 0.951mols). Allowed to exotherm to 50°C. Heated with an aluminum block for 1 hour at a pot temperature of 65°C. Cloudy throughout. Increased temperature to distill off methanol to a pot temperature of 95°C. Amount of volatiles removed: 53.9g. Diluted to about 75% with xylene (36.67g). Clear. While mixing, added a solution containing (0.122g 45% KOH(aq) in 1g methanol) at room temperature. This amount of KOH corresponds to about 500ppm based on theoretical yield. Heated with an aluminum block. Onset time was measured from when volatiles first began to collect in the Dean Stark apparatus, which corresponds to a pot temperature of 91°C. Heated to 115°C and then allowed to stand at this temperature. Volatiles removed: 30 min = 9.32g, 1 hr = 10.72g, 2 hr = 11.86g, no volatiles collected after 2 hr. Total time = 12 hr. 13C NMR analysis of 5 hr sample showed approximately 35% of MePhPrOH had reacted to silicon. 13C NMR analysis of 12 hr sample showed approximately 46% of MePhPrOH had reacted to silicon. Added additional HCl solution (1.38g of solution) at room temperature. Stoichiometry 1.05 mols HCl: 1.0 mols KOH. Mixed overnight at room temperature. Stripped product on rotary evaporator at 120°C oil bath temperature and approximately 2mmHg. Pressure filtered through Osmonics MAGNA Nylon Supported Plain 0.45um filter (47mm diameter) at room temperature. The filtration rate was slow; only 80-90% of the material was filtered.

[0058] Results: The product was a clear, pale yellow viscous liquid at room temperature. Isolated yield: 91.3 g. 13 Amine equivalent weight calculated from C NMR spectrum: 229 g / mol NH. NMR analysis of the product: T PrNH2 0.233 T Me0.767 OZ content: 63.8 mol%; (51.3 mol% OMe, 12.5 mol% MePhPrO); 17.5 wt% MePhPrO; 9.1 wt% phenyl (from MePhPrO); Si molar ratio and OR values ​​derived from 13C NMR data.

[0059] S5: DTPh resin reacted with amino-propanol Reagents: Dowsil™ 3074-D available from The Dow Chemical Company 0.337 T シクロヘキシル 0.010 T Ph 0.653 ;OZ=68.64mol%;FW approx. 126.5g / mol Si 1-Amino-2-propanol - Mw=75.11, bp=160℃

[0060] procedure: A 250 mL single neck round bottom flask was charged with Dowsil™ 3074 (94.19 g, 0.745 mols Si. 0.511 mols OZ) and 1-amino-2-propanol (16.52 g, 0.220 mols, 0.440 mols NH). The flask was equipped with a magnetic stir bar and a Dean Stark apparatus attached to a water cooled condenser. The mixture was not miscible at room temperature. Heat at 140° C. aluminum block temperature for 2 hours. The amount of volatiles collected at the first hour was 3.35 g and at the second hour was 0.31 g. During heating to 140° C., the reaction mixture became clear. The block temperature was increased to 180° C. This temperature was held for 2 hours. The amount of volatiles collected at the first hour was 1.85 g and at the second hour was 0.13 g. The product was stripped on a rotary evaporator at an oil bath temperature of 115° C. and approximately 1 mm Hg.

[0061] Result: The product was a clear viscous liquid at room temperature. Isolated yield: 100.9 g. 13 Amine equivalent weight calculated from C NMR spectrum: 256 g / mol NH. NMR analysis of the product: D0.333 T シクロヘキシル 0.007 T Ph 0.660 OZ content: 61.95 mol% 26.9 mol% OR; 33.5 mol% OMe. The above two OR values ​​were calculated from 13C NMR by taking the ratio of the OR integrals and dividing it by the integral of the phenyl group.

[0062] S6: Me-T resin reacted with 1-amino-2-propanol without aryl functionality Reagents: Dowsil™ CF-2403 Methyl-T Resin-D available from The Dow Chemical Company 0.015 T Me 0.985 FW=93.4g / mol Si; OMe=113.6mol% 1-Amino-2-propanol - Mw=75.11, bp=160℃

[0063] procedure: A 250 mL 2-neck round bottom flask was charged with Dowsil™ CF-2403 (80.0 g, 0.857 mols Si, 0.973 mols OMe) and 1-amino-2-propanol (14.47 g, 0.193 mols). The flask was equipped with a magnetic stir bar, nitrogen applied, nitrogen blanket, and a Dean Stark apparatus attached to a water-cooled condenser. The reaction mixture was cloudy at room temperature. Heating was performed using an aluminum block. The onset time was measured from when volatiles first began to collect in the Dean Stark apparatus, which corresponds to a pot temperature of 101° C. Heat to 125° C. and then hold at this temperature. Total time=4 hours. During heating, at approximately 60° C., the reaction mixture became clear. Volatiles removed: 30 min—5.97 g; 1 h—6.00 g. No volatiles were collected after 1 h. The product was stripped on a rotary evaporator at an oil bath temperature of 70° C. and approximately 2 mm Hg.

[0064] Result: The product was a clear, low viscosity liquid at room temperature. Yield: 76.4 g.13 Amine equivalent weight calculated from the C NMR spectrum: 241 g / mol NH. The amine equivalent weight was calculated from the C NMR data using the average of two carbons in the C NMR spectrum (approximately 20 ppm and approximately 70 ppm) and CDCl3 as an internal reference. Integrals (9.38 and 8.62). NMR analysis of the product: 0.010 T Me 0.990 Total OZ content: 100.3 mol% (20.6 mol% OR; 79.7 mol% OMe) OR = 1-amino-2-propanol reacted with silicon.

[0065] Coating formulation: Clear coating The clear coating compositions in Table 3 were prepared in the following manner: the acrylic copolymer was placed in a MAX 40 SpeedMixer™ cup, the amino-functional silicone resin was added, and mixed in a FlackTek™ DAC150 SpeedMixer™ for 2 minutes at 2000 rpm. In formulating the coating compositions, the acrylic copolymer and the amino-functional silicone resin are added in amounts that provide a 1:1 epoxy / NH molar ratio. [Table 3]

[0066] The Tg of the coating was measured using DSC (first heat at 20° C. / min) and determined after 10 days of moisture cure.

[0067] A comparison of CTG1, CTG2 and CTG5 in Table 2 illustrates the advantages of the present invention. CTG1 contains 21 mol% phenyl groups, CTG2 contains 22 mol% phenyl groups and CTG5 contains 66 mol% phenyl groups. Comparative CTG5 contains a higher mol% phenyl group than CTG1 or CTG2 and incorporates this group through a SiC bond, but the coating is cloudy, which translates to inferior properties. CTG1 and CTG2 show that the incorporation of phenyl groups through SiOC bonds can provide high quality, optically clear coatings even with lower aryl group incorporation than the SiC bonded versions. The industrial applicability of the present invention cannot be underestimated considering the lower cost of SiOC-based resins compared to SiC-based resins.

[0068] How to apply clear coat withdrawal Coatings were applied to Q-Panel R-412-I (phosphate-treated cold rolled steel) and AL412 (chromate-treated aluminum) panels in accordance with ASTM D4147. The panels were secured to a firm, level surface using a magnetic chuck or clamp. A multi-clearance square applicator was used to apply the coatings to the panels to achieve the desired dry film thickness of approximately 2.5 mils, targeting a wet thickness of 5-6 mils.

[0069] Coating Application and Testing Methods Withdrawal Procedure The coating was applied to a metal panel according to ASTM D4147-99 (2007). A magnetic chuck was used to secure the panel to a firm horizontal surface. A sufficient amount of coating was poured over the entire top edge of the panel and a 5 mil gap wet film applicator was used to draw the coating down the length of the panel towards the operator using uniform pressure and speed to apply a uniform film. The panels were allowed to cure in a controlled temperature and humidity laboratory at 72°F and 50% relative humidity.

[0070] Dry Time: The coating was drawn down onto a 1" x 12" glass substrate with a wet film thickness of 76 micrometers (μm) and a BYK Dry Time Recorder was set up. Tack-free, tack-free time, and dry hardness were measured by dragging a needle through the coating using a BYK Dry Time Recorder according to ASTM D5895-03.

[0071] Pendulum Hardness: Pendulum hardness was measured using a BYK Gardner pendulum hardness tester equipped with a Konig pendulum. The tester was run according to ISO 1522 and set to measure hardness in seconds.

[0072] pencil hardness The pencil hardness of the coating film is measured according to the ASTM D3363 method. The coating composition is applied to a glass panel to form a wet film with a thickness of 120 microns and cured at room temperature for 7 days. The resulting film is then tested by Zhonghua pencil. The hardness of the pencils used are 9H, 8H, 7H, 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, 6B, where 9H is the hardest and 6B is the softest.

[0073] Gloss: The 20°, 60°, and 85° gloss of the coatings were measured according to ASTM D-523-89 using a BYK Gardner Micro TRI Glossmeter.

[0074] Methyl Ethyl Ketone Double Rub Test: Methyl Ethyl Ketone (MEK) double rub tests were performed according to ASTM D5402 using a semi-automatic MEK rub tester manufactured by DJH DESIGNS INC. The test was continued until the coating rubbed down to the substrate or until a maximum of 200 double rubs were completed without failure.

[0075] The performance properties of the coating compositions are shown in Figure 4. Ctg1 and Ctg2 compared to Ctg7 and Ctg8, respectively, illustrate the importance of cure compatibility groups (e.g., HEMA) in the acrylic copolymer providing improved pencil hardness, improved dry time, improved gloss readings, improved hardness, and improved MEK resistance. [Table 4]

Claims

1. 1. A curable coating composition comprising: (1) In polymerized form (i)(R 3 SiO 1/2 ) a 、 (fm)(R 2 Si(OR') x O (2-x)/2 ) b 、 (iii) (RSi(OR') y , O (3-y)/2 ) c , and (iv)(Si(OR') z O (4-z)/2 ) d wherein each R' is independently hydrogen, an alkyl group, a functionalized alkyl group, a benzyl group, a sec-phenethyl group, a 2-phenylethyl group, a 2-phenyl-2-methylethyl group, or a 2-methyl-1-phenyl-2-propyl group, provided that at least 10 mole percent of all R' groups are benzyl, sec-phenethyl, 2-phenylethyl, 2-phenyl-2-methylethyl, or 2-methyl-1-phenyl-2-propyl groups; wherein each R is independently hydrogen, an alkyl group, or a functionalized alkyl group; wherein at least 10 mole percent of the combined R and R′ groups are of the formula: -Ra-NHR b where R is an amine-containing group of the formula a is an alkyl group derived from an amino alcohol, R b is hydrogen or an alkyl group, wherein a+b+c+d=1.00 (100 mole percent), x is either 0 or 1, y is either 0, 1, or 2, and z is either 0, 1, 2, or 3; an amino-functional silicone resin having an —NH— equivalent weight of 50 to 750; (2) an acrylic copolymer having, in polymerized form, epoxy-functionalized groups and cure-compatible groups; The curable compatible group is a monomer group containing an alcohol (OH) functional group; A curable coating composition, wherein said coating composition has a molar ratio of amine NH functional groups to epoxy functional groups in the range of 0.5 to 1.

3.

2. 10. The coating composition of claim 1 having a molar ratio of amine NH functional groups to epoxy functional groups in the range of 0.8 to 1.

3. At least 20 mole percent of the combined R and R′ groups of the amino-functional silicone resin are represented by the formula: a -N.H.R. b 2. The coating composition of claim 1, wherein the R' group is an amine-containing group of the formula:

4. From 5 to 42 mole percent of said combination of R and R′ groups of said amino-functional silicone resin are represented by the formula: a -N.H.R. b 2. The coating composition of claim 1, wherein the R' group is an amine-containing group of the formula:

5. The coating composition of claim 1 , wherein the amino alcohol is a secondary or tertiary alcohol.

6. The coating composition of claim 1, wherein the amino alcohol is 1-amino-2-propanol or 1-amino-2-methylpropan-2-ol.

7. 2. The coating composition of claim 1, wherein 20 to 50 mole percent of all R' groups are benzyl, sec-phenethyl, 2-phenylethyl, 2-phenyl-2-methylethyl, or 2-methyl-1-phenyl-2-propyl groups.

8. 2. The coating composition of claim 1, wherein the epoxy functionalized groups of the acrylic copolymer are derived from one or more monomers selected from the group of glycidyl methacrylate (GMA), glycidyl acrylate, and mixtures thereof, and the acrylic copolymer has an epoxy equivalent weight (EEW) in the range of 200 to 600.

9. The coating composition of claim 8, wherein the acrylic copolymer comprises 30 to 60 weight percent glycidyl (meth)acrylate monomer units in polymerized form, based on the weight of total monomer units of the acrylic copolymer.

10. 10. The coating composition of claim 1, wherein the acrylic copolymer comprises from 2% to 20% by weight, in polymerized form, of cure compatible group monomer units, based on the weight of the total monomer units of the acrylic copolymer.

11. The coating composition of claim 1 , wherein the cure compatible groups are derived from hydroxyethyl methacrylate (HEMA).

12. A coated article comprising one or more layers of the cured coating composition of claim 1.

Citation Information

Patent Citations

  • Method for forming coating film

    JP1997302286A

  • Coating composition

    JP2002309165A

  • Amino-functional polysiloxane and its use in coating agents

    JP2005529198A

  • Coating composition having an alkoxy-containing amino-functionalized silicone resin

    JP2013515090A

  • Low temperature curable coating compositions and related methods

    US20090234071A1